A systematic literature review of film title translation - Hu, Xiaojing; Abdul Halina, Hazlina; Mohd Zin, Zaid (Academy Publication, 2025)
—Film titles play a pivotal role in encapsulating films’ plot, mood, and character, making them critical for attracting audiences and promoting films effectively. They rightly deserve more extensive and systematic linguistic research. Film title translation study has received much attention from many scholars, and their findings have been published, including translation strategies, linguistic features, and theoretical frameworks applied to film title translation in many languages. Despite extensive research on film title translation, gaps remain, including repetitive content and a lack of interdisciplinary perspectives. For this reason, it is necessary to carry out a systematic literature review of film title translation. This systematic review examines 55 journal articles published between 1993 and 2024, focusing on publication trends, thematic scope, and key findings in the field of film title translation. Utilizing Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines and data from Scopus, Linguistic Abstracts, and Web of Science, the review highlights an increasing trend in multilingual studies involving 18 languages and underscores the limited theoretical advancements and focus on translation challenges. The study shows that few studies have focused on the translation problems of film titles, and theory development is limited. Future research should explore genre-specific film titles and adopt corpus-assisted approaches to better analyze naming patterns and translation strategies.